Exploring views on affective haptic devices in times of COVID-19 - Ipakchian Askari, Sima; Huisman, Gijs; Haans, Antal; IJsselsteijn, Wijnand A. (Frontiers in Computer Science, 2022)
Affective haptic devices (AHDs) are communication technologies utilizing the sense of touch, and include mediated social touch (MST), symbolic haptic messaging, and awareness systems that, for example, let one feel another person’s heartbeat. The COVID-19 pandemic and consequent social distancing measures have led to a reemphasis of the importance of social touch, and many people have experienced firsthand what it is like to miss touching loved ones. This offers an excellent opportunity to study people’s intention to use AHDs. For this purpose, a survey study was conducted combining qualitative and quantitative data analysis methods. Touch deprivation, resulting from not being able to touch a loved one, was associated with intention to use AHDs: the more deprived the individual, the higher their intention to use AHDs. Technology readiness and touch aversion did not affect intention to use AHDs. AHDs for symbolic messaging gained higher interest than MST and awareness devices, and long-distance relationships were seen as the most likely scenario for using AHDs. Bi-directionality, synchronicity, and symmetry were regarded as important features for providing shared meaning and a sense of connectedness. Reviewability, multimodality, and actuation type were also deemed important. Limitations of the study and implications for the design of AHDs are discussed.